FAKTOR-FAKTOR YANG MEMPENGARUHI NIAT DAN PERILAKU MAHASISWA BISNIS DI INDONESIA DALAM MENGADOPSI TEKNOLOGI ARTIFICIAL INTELLIGENCE (AI): PENDEKATAN INTEGRATIF TAM DAN UTAUT - Frasto Biyanto; Deden Iwan Kesuma; Rudy Badrudin; Yusti Pujisari (KRISNA: Kumpulan Riset Akuntansi, 2026)
The application of artificial intelligence (AI) technology in higher education has become a strategic need, especially for business students who have technology-based professional needs. This study aims to analyze the factors that influence students' intentions and actual behavior in adopting AI by integrating two main theoretical models, namely the Technology Acceptance Model (TAM) and the Unified Theory of Acceptance and Use of Technology (UTAUT). This study involved 365 business university students as respondents from various regions in Indonesia and was analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) approach. The results of the analysis show that Perceived Effectiveness (PU) and Social Influence (SI) have a significant positive effect on Intention to Use (IU), which in turn becomes the main predictor of Actual Use (AU) of AI. In contrast, Perceived Ease of Use (PEOU) does not show a significant effect on IU, indicating that ease of use is no longer a major factor for the digital-native generation. The moderation test shows that gender does not act as a moderator in the relationship between IU and AU. This study confirms that the adoption of AI is not only determined by the functional aspects of technology but also by the perception of benefits and social influence. These findings provide theoretical contributions through the TAM–UTAUT integrative development model, as well as practical implications for educational institutions in designing more effective and adaptive technology adoption strategies to the characteristics of today's student generation